Pengisian Identitas Profesional Pemberi Asuhan pada Berkas Rekam Medis Berdasarkan Standar Akreditasi di Rumah Sakit Umum Haji Medan - Karo, Siddik Karo; Tia Mufida Muthmainnah Siregar; Ritonga, Zulham Andi (Jurnal Siti Rufaidah, 2025)
Accreditation is the recognition of the quality of hospital services after an assessment has been conducted to determine whether the hospital has met accreditation standards approved by the government. Every note in the medical record must clearly identify the professional care provider (PPA), including the full name and signature, as well as the date and time of writing. The purpose of this study was to determine how the PPA's identity is filled in in medical records based on accreditation standards at Haji General Hospital, Medan. The research method used was qualitative research, with data collection techniques using in-depth interviews and observation. Six informants participated, including doctors, nurses, and medical records officers. The results showed that despite the existence of Standard Operating Procedures (SOPs) for filling in the PPA's identity, incomplete medical records were still found, such as only including a signature without a clear name and an omitted date and time. Incomplete files were returned to the relevant unit for correction. The main obstacle faced was the PPA's limited working time to complete the medical record files. In conclusion, the PPA's identity is not fully compliant with existing SOPs. Therefore, regular monitoring and evaluation, along with training for all PPAs, are needed to ensure optimal completeness of medical record documentation.